2015
DOI: 10.7247/jtomc.2014.2136
|View full text |Cite
|
Sign up to set email alerts
|

Metamizole Related Granulocytopenia and Agranulocytosis: An Analysis of 13 Children

Abstract: Objectives: Metamizole sodium (Novalgin ® ) is an effective, widely used analgesic and antipyretic agent in several countries. In spite of its availability and common usage, it has serious and potentially fatal adverse effects like agranulocytosis and aplastic anemia. Objectives of this study are to evaluate incidence, severity, and clinical significance of metamizole related neutropenia and agranulocytosis, and to study recovery duration of neutropenia and agranulocytosis in children exposed to metamizole. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…During this period, granulocytopenia and agranulocytosis were detected in 13 children. The study results revealed that the incidence of metamizole-related agranulocytosis in pediatric patients admitted to the hospital was 1/10,000, and it was suggested that clinicians should not consider metamizole as the fi rst-line therapy in the paediatric population (11). Agranulocytosis was detected in one of the two cases with metamizole-related adverse effects in Antalya, Turkey.…”
Section: Discussionmentioning
confidence: 94%
“…During this period, granulocytopenia and agranulocytosis were detected in 13 children. The study results revealed that the incidence of metamizole-related agranulocytosis in pediatric patients admitted to the hospital was 1/10,000, and it was suggested that clinicians should not consider metamizole as the fi rst-line therapy in the paediatric population (11). Agranulocytosis was detected in one of the two cases with metamizole-related adverse effects in Antalya, Turkey.…”
Section: Discussionmentioning
confidence: 94%